2002
DOI: 10.1038/sj.ejcn.1601359
|View full text |Cite
|
Sign up to set email alerts
|

Reasons among older Swedish women of not participating in a food survey

Abstract: Objectives: To (a) examine participation rate as a function of municipality, age group and living status; and (b) investigate the main reasons for exclusion and declining as stated by the women themselves. Design: Analysis of participation rate and content analysis of statements given in phone calls explaining exclusion or declination from a project in which 24 h recalls and food-diaries were used. Subjects: Self-managing Swedish women (n ¼ 505) were systematically selected from a stratified random sample cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…A number of the residents who declined participation declared that no one had earlier shown an interest in the elderly and frail and they expressed no wish to tell others about their situation. This is in agreement with Sidenvall et al (2002) who reported that the four most common reasons for declining participation in a food survey among elderly women were lack of time, tiredness, unwillingness to participate in scientific studies and increased age and therefore had no contribution to make.…”
Section: Discussionsupporting
confidence: 91%
“…A number of the residents who declined participation declared that no one had earlier shown an interest in the elderly and frail and they expressed no wish to tell others about their situation. This is in agreement with Sidenvall et al (2002) who reported that the four most common reasons for declining participation in a food survey among elderly women were lack of time, tiredness, unwillingness to participate in scientific studies and increased age and therefore had no contribution to make.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is known that it is difficult to include older persons in surveys. Sidenvall et al51 found that those older people who were most active or very ill and disabled did not want to participate. In our study, there is a possibility that the group of nonparticipants had more health problems than the participants and therefore was not able to answer the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…To be able to participate in this study by using a mailed questionnaire, a necessary qualification for the participants, was a sufficient cognitive ability. It is also an important aspect to be aware of that eating habits may be difficult and too personal to report 27,51…”
Section: Discussionmentioning
confidence: 99%
“…Further, calcium intake was below the recommended level in the part-cooking and nocooking groups. Mean intakes of vitamin B 6 , B 12 and C were above recommended levels in all groups. Nutrient density was satisfactory except for folate in all groups, and slightly below recommended for vitamin E in the cooking and part-cooking groups.…”
Section: Intakes Of Energy Selected Nutrients and Dietary Brementioning
confidence: 92%